Controlling confounding by frailty when estimating influenza vaccine effectiveness using predictors of dependency in activities of daily living. Issue 12 (24th August 2017) - Zhang, Henry T.; McGrath, Leah J.; Wyss, Richard; Ellis, Alan R.; Stürmer, Til
Abstract: Purpose: To improve control of confounding by frailty when estimating the effect of influenza vaccination on all‐cause mortality by controlling for a published set of claims‐based predictors of dependency in activities of daily living (ADL). Methods: Using Medicare claims data, a cohort of beneficiaries >65 years of age was followed from September 1, 2007, to April 12, 2008, with covariates assessed in the 6 months before follow‐up. We estimated Cox proportional hazards models of all‐cause mortality, with influenza vaccination as a time‐varying exposure. We controlled for common demographics, comorbidities, and health care utilization variables and then added 20 ADL dependency predictors. To gauge residual confounding, we estimated pre‐influenza season hazard ratios (HRs) between September 1, 2007 and January 5, 2008, which should be 1.0 in the absence of bias. Results: A cohort of 2 235 140 beneficiaries was created, with a median follow‐up of 224 days. Overall, 52% were vaccinated and 4% died during follow‐up. During the pre‐influenza season period, controlling for demographics, comorbidities, and health care use resulted in a HR of 0.66 (0.64, 0.67). Adding the ADL dependency predictors moved the HR to 0.68 (0.67, 0.70). Controlling for demographics and ADL dependency predictors alone resulted in a HR of 0.68 (0.66, 0.70). Conclusions: Results were consistent with those in the literature, with significant uncontrolled confounding after adjustment for demographics, comorbidities, and health care use. Adding ADL dependency predictors moved HRs slightly closer to the null. Of the comorbidities, health care use variables, and ADL dependency predictors, the last set reduced confounding most. However, substantial uncontrolled confounding remained.